Seismic design and performance of multi-tiered steel braced frames including the contribution from gravity columns under in-plane seismic demand. (November 2016) - Imanpour, Ali; Auger, Karl; Tremblay, Robert
Abstract: This paper examines the possibility of mobilizing gravity columns in the resistance of in-plane bending moments imposed on the columns of multi-tiered steel braced frames subjected to seismic loading. This would be the case when horizontal struts are used to connect gravity columns to braced frames at every tier level, as is often seen along exterior walls. A seismic design strategy based on the AISC Seismic Provisions is presented for four-tiered prototype steel concentrically braced frames. Three different approaches are proposed for the design of the braced frame and gravity columns. A set of 12 four-tiered X-braced frames, ranging from 15 to 30 m in height and located in a high seismic area were designed based on the proposed design approaches. The seismic behavior of the frames is evaluated using nonlinear response history analysis. The results show that the seismic performance of the braced frames is improved as nonlinear seismic demand on the bracing members is reduced when mobilizing the gravity columns for lateral resistance. Furthermore, gravity columns bending moment demands are distributed between braced frame and gravity columns in proportion of their relative flexural stiffness. Adequate seismic performance and cost-effective design can be achieved when columns of both types are designed to resist their respective share of the flexural demand. Alternatively, satisfactory response was achieved when the gravity columns are verified for the seismic induced bending moments acting together with concomitant axial loads.